The prognosis of patients with atrial fibrillation is improved when sinus rhythm is restored: report from the Stockholm Cohort of Atrial Fibrillation (SCAF). Issue 12 (19th March 2009) - Friberg, L; Hammar, N; Edvardsson, N; Rosenqvist, M
Abstract : Background: Clinical trials have indicated that an active rhythm control strategy aiming at restoration of sinus rhythm in patients with atrial fibrillation (AF) is no better than a rate-control strategy in terms of mortality and morbidity. To what extent restoration and maintenance of sinus rhythm per se affect long-term prognosis in AF patients is less clear. Aim: To investigate if there are differences in mortality and morbidity between direct current (DC)-cardioverted AF patients who remain in sinus rhythm after cardioversion and those who relapse early. Method: 361 cardioverted patients from the Stockholm Cohort Study on Atrial Fibrillation were studied by means of medical records and national registers. Patients were followed for a mean of 4.2 years from DC cardioversion regarding all-cause mortality and for a mean of 3.2 years for a composite endpoint of death, ischaemic stroke, myocardial infarction or hospitalisation for heart failure. Results: All-cause mortality tended to be lower in patients who had been successfully cardioverted and had had no known relapse of AF within the first 3 months after cardioversion (hazard ratio (HR) 0.57, 95% CI 0.30 to 1.06, p = 0.076). They also had a significantly lower incidence of the composite endpoint than those who relapsed early (HR 0.51, 95% CI 0.32 to 0.82, p = 0.0058). Conclusion: Restoration and 3 months maintenance of sinus rhythm was associated with improved long-term prognosis. The results imply that an active DC cardioversion approach is justified.